Stevens Johnson Syndrome in Babylon (Indian Journal of Forensic Medicine & Toxicology, 2021)
SJS and TEN are emergency medical conditions, rare but with high mortality rate. They start as flu like illnesswith high fever. They are mucocutaneous disorders Affect mainly the skin, eye, nose, mouth and genitalia,with characteristics rash, blistering, peeling of the skin. Two accused as a cause: certain drugs, and infectionslike Mycoplasma pneumonia. In order to overcome the lack of informative studies about these syndromes,and to lower the high mortality rate associated, we followed the occurrence, diagnosis, management andprognosis of these syndromes in one year field study in the province of Babylon, Iraq from the 1st of March2018 to the 1st of March 2019. The data were taken from the medical records of 4 major hospital in thecenter of AL Hilla city, Iraq (Al Hilla teaching hospital , Merjan teaching hospital Babil teaching hospital,and Al Noor pediatric hospital). Five cases of this syndrome where reported, 3 males and 2 females with agerange 23-30 years. One female survived. Four patients died. Full typical autopsy with necessary laboratorytests where achieved in the department of Forensic Medicine in Babylon. The occurrence of this syndromewas 5 /2 million /year, the diagnosis was delayed and accordingly the management and lines of treatmentwere delayed too, leading to bad prognosis (four deaths, one survival). The mortality rate was 80%. Thedirect causes of death were pneumonia and encephalitis associated with Stevens Johnson Syndrome. Thissyndrome should be kept in mind when prescribing a medication. Early management is leading to goodprognosis
Keywords: Mortality; Occurrence; Steroids; TEN (toxic epidermal necrolysis)